(Re)Defining Fairy Tales: A Deontology Ethical Approach to Oscar Wilde’s Selected Fairy Tales - Chyu Vey Kiang; Soon Seng Foong (Universitas Muhammadiyah Metro, 2021)
Fairy tales are often used by authors to impart their moral values and principles. This is commonly done through the portrayal of their main characters, including their personalities, actions, and the consequences of their actions. In some cases, authors use death as a moral lesson due to its connotation as a form of punishment for a character’s misdeed. However, Oscar Wilde’s fairy tales contradict the conventional aspect of death in classic fairy tales. His main characters experienced death or physical disfigurement in the end despite their actions which readers would perceive as good or morally permissible. Therefore, this study aims to investigate the theme of morality in Wilde’s selected fairy tales through a Deontology Ethical approach. This study addressed the relationship between the personalities and actions of Wilde’s selected characters, as well as the consequences of their actions. Furthermore, using Kantian Ethics, the study evaluated the moral permissibility of the characters’ maxims underlying their actions. The findings showed that the personalities of Wilde’s characters could be categorised into those who adhere to or oppose Kant’s definition of personality based on their actions. The study also highlighted the varying deaths that Wilde’s characters faced in the end. Additionally, the analysis suggests that the reasons behind the actions of Wilde’s characters could be categorised into “for duty” and “for other means”. At the end of this study, readers would be introduced to a different moral theory in understanding a character without justifying it based on the simple “right versus wrong” principle.